Gendered implications of restricted residence obligation policies on refugees' employment in Germany - Adriana R. Cardozo Silva; Yuliya Kosyakova; Aslıhan Yurdakul (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper investigates the gender-specific impact of settlement policies on the labor market integration of refugees in Germany, utilizing a gender-specific approach. Analyzing data from the IAB- BAMF-SOEP Refugees Survey (2016-2020) through a pooled logit model with an intention-to-treat design, we explore how restrictive residency obligation policies, in conjunction with local conditions in the assigned county-such as local labor market conditions and ethnic enclaves - influence outcomes. Results reveal that female refugees experience reduced employment prospects, independent of mobility restrictions, while the residency obligation policy bears a significant negative impact on employed male refugees. In turn, the impact of analyzed local labor market characteristics and linguistic enclaves on employment probability remains consistent across gender and residency obligation. Our results highlight the multidimensional nature of refugees' labor market integration and underscore the significance of gender-sensitive approaches.
Keywords: 330